GGE and Ammi Biplot Analysis for Field PEA Yield Stability in Snnpr State, Ethiopia - Rezene, Yayis; Bekele, Agdew; Goa, Yasin (International Journal of Sustainable Agricultural Research, 2014)
The experiment was conducted for two consecutive years across four locations using 16 field pea genotypes. The objective of this paper is to determine the magnitude of genotype by environment interactionand performance stability of genotypes. Analysis of variance (ANOVA), regression of genotype on the environmental mean, AMMI analysis, ASV estimation and GGE biplot analysis were carried out following their respective procedures. Pooled analysis of variance for grain yield showed significance differences among genotypes, environments and G xE interaction. This implied genotypes differently responded to change in environments. Both ASV and AMMI biplot analysis showed the same result in identifying the widely adapted genotypes. Genotypes IG-51700 and SAR-FB-61 were the best adapted ones in this experiment for wide scale recommendation in field pea growing areas while Genotype FP-Milky was better adapted variety in the high potential areas, like Angecha, which is already under production. Based on the GGE biplot analysis, Angecha o4 environment is more discriminating environment than others for the superior genotype selection. Location-wise Waka provided little or no information about the genotypic differences, therefore, should not be considered as test environments for field pea yield trials. Angecha, Hosanna and Bule can be efficiently used for filed pea multi-environment yield trials provided that they are further confirmed by multi-year experimental data.